Debottlenecking of an in vitro enzyme cascade using a combined model‐ and experiment‐based approach - Siedentop, Regine; Dziennus, Marlon; Lütz, Stephan; Rosenthal, Katrin (Technische Universität Dortmund, 2023)
Designing a feasible in vitro enzyme cascade is a challenging task that is often preceded by optimization steps. Computational methods can increase the efficiency of the optimization process by providing a deeper insight into the system. In this study, bottlenecks of a farnesyl pyrophosphate-producing in vitro enzyme cascade were determined by a combination of in silico modeling and wet-lab experiments. ATP and the precursor-isomerizing enzyme isopentenyl diphosphate δ-isomerase were identified as limitations of the in vitro enzyme cascade.
Chemie - Ingenieur - Technik; 95(4)
Keywords: Biocatalysis; Enzyme cascades; In vitro biotransformations; Kinetic models; Terpenes; 660